Baseline and on‐treatment HBcrAg levels as predictors of HBeAg seroconversion in chronic hepatitis B patients treated with antivirals. Issue 1 (11th November 2022) - Hwang, Soo Young; Yoo, Sung Hwan; Chang, Hye Young; Kim, Sora; Lee, Jung Il; Lee, Kwan Sik; Cho, Young Youn; Joon, Kim Hyung; Lee, Hyun Woong
Abstract: HBeAg seroconversion is an important treatment endpoint. We aimed to identify predictors of seroconversion using serum HBsAg and hepatitis B core‐related antigen (HBcrAg) in HBeAg‐positive patients treated with nucleos(t)ide analogs (NAs). Data and samples from 70 HBeAg‐positive patients treated with entecavir or tenofovir between January 2007 and December 2017 were retrospectively analysed. The mean follow‐up period was 11 years. The predictive power for HBeAg seroconversion of HBcrAg levels at baseline and 2 years after antiviral therapy was determined using receiver operating curve analysis. Twenty‐one patients (30%) achieved HBeAg seroconversion at a mean of 28 (range, 12–84) months after antiviral treatment. The median baseline HBcrAg and HBsAg levels were 6.9(5.7–7.0) vs. 5.8(5.5–6.5) log10 U/mL ( p  = .006), 4.9(4.5–5.1) vs. 4.5(4.1–5.0) log10 IU/mL ( p  = .044) in the no seroconversion group and seroconversion group, respectively. In the multivariate analysis, the serum HBcrAg levels at baseline and 2 years after antiviral therapy were predictive factors for HBeAg seroconversion ([HR]; 0.326; [CI], 0.111–0.958; p  = .042 and HR, 0.4555; CI, 0.211–0.984; p  = .045). HBcrAg levels≤6.5log10 U/mL at baseline and ≤5.3log10 U/mL at 2 years after antiviral therapy had sensitivities of 53.1% and 69.8%, specificities of 95.2% and 70.6%, positive predictive values of 82.6% and 50.0%, and negative predictive values of 82.6% and 84.5%, respectively, with AUROCs of 0.712 (95%CI, 0.596–0.830) and 0.745 (95%CI, 0.599–0.891) for predicting HBeAg seroconversion. In chronic hepatitis B patients treated with NAs, HBcrAg levels≤6.5log10 U/mL at baseline and ≤5.3log10 U/mL at 2 years after antiviral therapy were useful predictive factors of HBeAg seroconversion.